Faktor-Faktor Yang Mempengaruhi Audit Report Lag: Pengaruh Umur Perusahaan, Ukuran Perusahaan Dan Reputasi Auditor - Luthfi Ajisantoso; Cris Kuntadi (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research functions to strengthen theories and phenomena of the relationship or influence between variables. This article reviews the factors that influence audit report lag, namely the influence of company age, company size and auditor reputation, a study of the tax accounting literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this article's literature review are: 1) the influence of company age on audit report lag; 2) company size influences audit report lag; and 3) the auditor's reputation influences audit report lag